2020
DOI: 10.1111/soin.12406
|View full text |Cite
|
Sign up to set email alerts
|

Who Are the Liberal Gun Owners?

Abstract: In the recent renaissance of interest in guns among sociologists, studies of the political conservatism of gun owners have proliferated, but we still know very little about politically liberal gun owners. This despite the fact that one in five U.S. gun owners (some 12 million adults) self‐identifies as liberal. This exploratory study, therefore, seeks to understand what seems on the surface to be an interesting and not rare category in American society: the liberal gun owner. In particular, we seek to answer t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
19
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 17 publications
(22 citation statements)
references
References 30 publications
3
19
0
Order By: Relevance
“…Warner (2020) found that participants who identified as men were significantly more open to future gun ownership, but only women had a significant association between perceived risk of crime and openness to gun ownership. This complexity partly confirms research (Mencken and Froese 2017; Yamane et al 2021) that different groups of gun owners have different underlying reasons for their gun ownership.…”
Section: Theory and Literaturesupporting
confidence: 78%
See 2 more Smart Citations
“…Warner (2020) found that participants who identified as men were significantly more open to future gun ownership, but only women had a significant association between perceived risk of crime and openness to gun ownership. This complexity partly confirms research (Mencken and Froese 2017; Yamane et al 2021) that different groups of gun owners have different underlying reasons for their gun ownership.…”
Section: Theory and Literaturesupporting
confidence: 78%
“…While gun owners largely remain white, middle-class, male, and Protestant relative to the U.S. population (Gallup, Inc. 2020; Legault and Lizotte 2009; Yamane, DeDeyne, and Méndez 2021), their demographics are shifting. Fewer new owners grew up with guns; new gun owners more often own handguns and identify as liberal, women, and nonwhite (Wertz et al 2018).…”
Section: Theory and Literaturementioning
confidence: 99%
See 1 more Smart Citation
“…David Yamane (2017) showed that the gun culture was not monolithic and coined the terms gun culture 1.0 (the recreational one) and gun culture 2.0 (self-defense). In a more recent article, David Yamane et al (2021) focused on liberal gun owners, showing that they could be treated as a separate category within the population of gun owners as opposed to their being a point on a continuum. Boine et al (2020) divided the gun culture into three elements: recreation, self-defense, and Second Amendment advocacy.…”
Section: Introductionmentioning
confidence: 99%
“…For example, although the most typical gun owner may be politically conservative, the majority are not. One-in-five gun owners in America self-identify as politically liberal and another 40 percent see themselves as politically moderate (Yamane, DeDeyne, and Aravena Méndez 2021). This is especially true of new gun owners.…”
Section: Understanding the Diversity And Complexity Of Gun Ownersmentioning
confidence: 99%